2023
DOI: 10.1097/md.0000000000033086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-administration of esketamine intraoperatively on postpartum depression after cesarean section: A randomized, double-blinded controlled trial

Abstract: Background: To evaluate the effect of pre-administration of esketamine intraoperatively on the occurrence of postpartum depression after cesarean section under combined spinal-epidural anesthesia. Methods: A total of 120 women aged 24 to 36 years undergoing cesarean section by spinal-epidural anesthesia with American Society of Anesthesiologists physical status II were enrolled. According to the intraoperative use of esketamine, all participants were randomly divided into 2 groups: test group (group E) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Our results were generally consistent with previous work investigating the effects of low dose ketamine2122 or esketamine on postpartum depression, mainly in mothers after caesarean delivery 2324252627. In a retrospective analysis of 240 mothers close to childbirth, esketamine administered for postoperative analgesia (mean 0.35 mg/kg during a 24 hour period) was associated with lower Edinburgh postnatal depression scale scores at three months 24.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results were generally consistent with previous work investigating the effects of low dose ketamine2122 or esketamine on postpartum depression, mainly in mothers after caesarean delivery 2324252627. In a retrospective analysis of 240 mothers close to childbirth, esketamine administered for postoperative analgesia (mean 0.35 mg/kg during a 24 hour period) was associated with lower Edinburgh postnatal depression scale scores at three months 24.…”
Section: Discussionsupporting
confidence: 91%
“…In a trial of 375 mothers about to give birth, esketamine given by way of patient controlled intravenous analgesia (at a rate of 0.25 mg/kg/day) for 48 hours lowered the prevalence of depression by 60% at 14 days 25. Two small trials reported that a single intraoperative dose of esketamine (0.2 or 0.5 mg/kg) decreased the prevalence of depression at 42 days by 73% and 58%, respectively 2326. Two other trials enrolled patients with Edinburgh postnatal depression scale scores of ≥10; one found that perioperative esketamine (0.25 mg/kg intraoperatively followed by 1-2 mg/kg postoperatively over 48 hours) reduced the prevalence of depression by 63% to 76% at seven days and by 49% to 67% at 42 days after caesarean delivery27; another study reported that intraoperative esketamine (0.3 mg/kg) lowered Edinburgh postnatal depression scale scores at seven and 42 days after curettage surgery 48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that administration of esketamine does not prevent the occurrence of PPD [28,29]. However, more studies have found that either single intravenous administration of esketamine [30] or using in PCIA can reduce the occurrence of PPD [4,31,32]. A recent study using traditional logistic regression and machine learning models also recommended esketamine for the treatment of PPD [33].…”
Section: Ppd Is a Relatively Common Postpartum Mental Disorder With A...mentioning
confidence: 99%
“…A recent study using traditional logistic regression and machine learning models also recommended esketamine for the treatment of PPD [33]. In previous studies, esketamine was given through intravenous injection [28][29][30]. Consistent with other studies, we found 0.2 mg/kg esketamine pumping for 40 min during cesarean section could reduce the occurrence of PPD 4 d postpartum and there was positive correlation between PPD scores at 4 d and 42 d, which suggested that the parturient with an early PPD was more likely to turn into a long-term PPD [4,7].…”
Section: Ppd Is a Relatively Common Postpartum Mental Disorder With A...mentioning
confidence: 99%